2005
DOI: 10.1111/j.1440-1797.2005.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the angiotensin converting enzyme and angiotensin II type 1 receptor genes and renal scarring in non‐uropathic children with recurrent urinary tract infection

Abstract: The results indicated that the ACE insertion/deletion and angiotensin II type 1 receptor gene polymorphisms were not independent risk factors for renal scar formation in recurrent urinary tract infection of paediatric patients without uropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
2
17
0
6
Order By: Relevance
“…This percentage seems to be higher than those reported in healthy Caucasian controls (DD: 24%) [8] and healthy Turkish controls (DD: 34%). [27] However, D allele frequency of our patients (66%) is in accord with the previous reports, giving the overall D (66.6%) and I (33.3%) allele frequencies in Turkish ESRD patients. [28] Distribution of the renin-angiotensin system polymorphism in children with VUR is well-studied, and its effect on renal scarring is of interest.…”
Section: Discussionsupporting
confidence: 80%
“…This percentage seems to be higher than those reported in healthy Caucasian controls (DD: 24%) [8] and healthy Turkish controls (DD: 34%). [27] However, D allele frequency of our patients (66%) is in accord with the previous reports, giving the overall D (66.6%) and I (33.3%) allele frequencies in Turkish ESRD patients. [28] Distribution of the renin-angiotensin system polymorphism in children with VUR is well-studied, and its effect on renal scarring is of interest.…”
Section: Discussionsupporting
confidence: 80%
“…Although we have not analyzed genetic susceptibility as the risk factor for ASL and USF several reports demonstrated the role of genetic susceptibilities as clinical determinants explain only a portion of individual risk [25]. Meta-analysis by Zaffanello et al revealed association between renal scarring formation after UTI and angiotensin enzyme insertion/deletion polymorphism or transforming growth factor-beta 1 c.509 T>C polymorphism [3,9,25].…”
Section: Discussionmentioning
confidence: 92%
“…The HWE was assessed in seven studies [38,39,42,43,46,50,51]. Calculation disclosed that seven studies presented a significant deviation from HWE [32,41,42,48,[51][52][53].…”
Section: Quality Of the Studiesmentioning
confidence: 99%
“…Most studies (67%) did not give a sufficient description of how they diagnosed UTIs in their patients, whereas six studies reported that the UTIs were diagnosed based on clinical and laboratory investigations [32,38,39,42,43,51].…”
Section: Quality Of the Studiesmentioning
confidence: 99%